Retrospective analysis of quantitative electroencephalography changes in a dissimulating patient after dying by suicide: A single case report - Rakús, Tomáš; Hubčíková, Katarína; Bruncvik, Lucia; Petrášová, Zuzana; Brunovsky, Martin (Frontiers in Psychiatry, 2023)
We present a case report of a 49-year old man diagnosed with depressive disorder, first episode with strong reactive factor. He was involuntarily admitted into a psychiatric hospital after a failed suicide attempt and he responded to psychotherapy and antidepressant therapy, as evidenced by a >60% reduction in MADRS total score. He was discharged after 10 days of treatment, denied suicidal ideations and was motivated to follow recommended outpatient care. Suicide risk during hospitalization was also assessed using suicide risk assessment tools and psychological assessment including projective test. Patient was examined again by outpatient psychiatrist on 7th day after discharge, including suicide risk assessment tool, again without found acute suicide risk or without worsening of depressive symptoms. On the 10th day after discharge, the patient committed suicide by jumping out of the window of his flat. We assumed that the patient had dissimulated his symptoms and suicidal tendency which were not detected despite repeated examinations aimed to suicidality and depression. We retrospectively analyzed his quantitative electroencephalography records to evaluate the change in prefrontal theta cordance as a potentially promising biomarker of suicidality, given the inconclusive results of studies published to date. An increase in prefrontal theta cordance value was found after the first week of antidepressant therapy and psychotherapy, in contrast to the expected decrease due to the fading of depressive symptoms. As demonstrated by the provided case study, we hypothesize that prefrontal theta cordance may be an EEG indicator of a higher risk of non-responsive depression and suicidal symptoms despite therapeutic improvement.